Fiber Lasers XV: Technology and Systems 2018
DOI: 10.1117/12.2290837
|View full text |Cite
|
Sign up to set email alerts
|

Cladding-pumped 70-kW-peak-power 2-ns-pulse Er-doped fiber amplifier

Abstract: An all-fiber pulsed erbium laser with pulse width of 2.4 ns working in a MOPA configuration has been created. Cladding pumped double clad erbium doped large mode area fiber was used in the final stage amplifier. Peculiarity of the current work is utilization of custom-made multimode diode wavelength stabilized at 981±0.5 nm -wavelength of maximum absorption by Er ions. It allowed us to shorten Er-doped fiber down to 1.7 m and keep a reasonably high pump-to signal conversion efficiency of 8.4%. The record outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Although we have deliberately selected an EDF that is partly quenched for our studies, similar Er 3+ -concentrations are possible with less quenching, as demonstrated with a P2O5:Al2O3:SiO2 glass matrix [11] (we estimate the fraction of unsaturable absorption to be half of that in our fiber). This allowed for pulse amplification with relatively high efficiency (8.4%) in a 1.7-m long EDF with a 35-μm core to 84 kW in 2-ns pulses [11] (energy extraction ~0.1 μJ/μm 2 /m).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we have deliberately selected an EDF that is partly quenched for our studies, similar Er 3+ -concentrations are possible with less quenching, as demonstrated with a P2O5:Al2O3:SiO2 glass matrix [11] (we estimate the fraction of unsaturable absorption to be half of that in our fiber). This allowed for pulse amplification with relatively high efficiency (8.4%) in a 1.7-m long EDF with a 35-μm core to 84 kW in 2-ns pulses [11] (energy extraction ~0.1 μJ/μm 2 /m).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of quenching, high-energy pulse amplification in rare-earth-doped fiber amplifiers, including EDFAs, is well understood [1][2][3][4][5][6][7][8][9][10][11]17,[45][46][47][48]. In the unquenched case, amplified spontaneous emission (ASE) or spurious lasing limits the energy that can be extracted (E extractable ) in a high-energy signal pulse to a few times the intrinsic saturation energy E IS , or say, at most 10 times [46][47][48] if the stored energy and the extraction efficiency are both at their practical limits.…”
Section: High-energy Pulse Amplification In Unquenched Fiber Amplifiersmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper describes the methodology for the estimation and management of these limiting factors for each amplifier stage. The work presented here is limited to the fibers which are commercially easily available, unlike customised Ybfree LMA erbium-doped fibers as mentioned in [4][5][6][7] or multifilament core fibers 7 . Inclusion of bulk optics such as gratings 8 shall be also avoided to have a robust all-fiber configuration.…”
Section: Introductionmentioning
confidence: 99%